Metal member, metal resin composite, method for manufacturing metal member and method for manufacturing metal resin composite
The metal member with a nano-column structure formed by pulsed laser irradiation addresses the insufficient sealing issue, achieving improved joint sealing performance with resin members.
Patent Information
- Application Number
- JP2023111839
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2043-07-07
AI Technical Summary
Conventional metal members do not have sufficient sealing performance when joined to a resin member, necessitating an improvement in joint sealing properties.
A metal member with a bonding region that includes a base layer with deposited debris particles and a two-dimensional nano-column body extending in the height direction, formed by pulsed laser irradiation to create a columnar group layer with an average height of 84 nm or more, enhancing the sealing performance when bonded to a resin member.
The enhanced nano-column structure improves the sealing performance at the joint between the metal and resin members, ensuring effective sealing and hermeticity.
Smart Images

Figure 2025009081000001_ABST
Abstract
Description
[Technical field]
[0001] The technical field disclosed in this specification relates to a metal member, a metal-resin composite, a method for manufacturing a metal member, and a method for manufacturing a metal-resin composite. [Background technology]
[0002] Metal-resin composites in which a metal member and a resin member are bonded are known. In order to improve the sealing property between the metal member and the resin member, the surface of the metal member is roughened in advance, for example, by a laser. For example, Patent Document 1 is an example of a related prior art.
[0003] Patent Document 1 describes the formation of nano-recesses having an opening width L and depth D on the submicron or nano-order on the surface of a metal member. In detail, the nano-recesses are formed so that the relationship between the opening width L and the depth D satisfies D / L≧1. In other words, protruding portions that cannot be said to be columnar portions are formed on the surface of the metal member as a whole. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-75805 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, conventional metal members do not provide sufficient sealing performance at the joint when joined to a resin member, and there is a demand for further improvement in sealing performance.
[0006] The present invention has been made in consideration of the above-mentioned circumstances, and its object is to provide a metal member and a manufacturing method for a metal member that have excellent sealing properties in the joint when joined to a resin member, as well as a metal-resin composite and a manufacturing method for a metal-resin composite that have excellent sealing properties. [Means for solving the problem]
[0007] The metal member made for the purpose of solving the above-mentioned problems is: A metal member having a bonding region on a surface thereof to which a resin member is bonded and which seals a gap between a first space and a second space together with the resin member, the bonding region includes a roughened region formed on the surface, in which a base layer is formed by the accumulation of debris particles, and a column group layer is formed in which the debris particles are linked together from the base layer in a string-like pattern to form nanocolumns that stand in a two-dimensional forest and extend in a height direction; The average height of the nanocolumns in the roughened region is greater than or equal to 84 nm.
[0008] According to the metal member of the present invention, the bonding area with the resin member includes a roughened region in which a base layer formed by the accumulation of debris particles and a column group layer in which debris particles are linked to the base layer in a string-like pattern and form a two-dimensional forest of nanocolumns extending in the height direction, the average height of the nanocolumns in the roughened region being 84 nm, thereby improving the sealing properties of the bonding portion when bonded to the resin member. [Brief description of the drawings]
[0009] [Figure 1] 1 is a perspective view of a battery according to an embodiment; [Diagram 2] 2 is a cross-sectional view taken along line AA in FIG. 1. [Diagram 3] FIG. [Figure 4] FIG. 2 is a perspective view of a unit member extracted from the battery of FIG. 1. [Diagram 5] 4A is a cross-sectional view taken along line BB in FIG. 4, and FIG. 4B is a cross-sectional view taken along line CC in FIG. [Figure 6]FIG. 1A is an explanatory diagram illustrating the bonding area between the upper surface of the lid member and the positive electrode resin member, and the area on the upper surface of the lid member that has been roughened; FIG. 1B is an explanatory diagram illustrating the bonding area between the lower surface of the lid member and the positive electrode resin member, and the area on the lower surface of the lid member that has been roughened. [Figure 7] FIG. 1A is an explanatory diagram illustrating a joint region between a side surface of a positive electrode terminal member and a positive electrode resin member, and a region on the side surface of the positive electrode terminal member that has been roughened; FIG. 1B is an explanatory diagram illustrating a joint region between an underside of a long straight portion of a positive electrode terminal member and a positive electrode resin member, and a region on the underside of a long straight portion of a positive electrode terminal member that has been roughened. [Figure 8] This is an image showing the actual formation of the foundation layer and pillar group layer. [Figure 9] This is an image showing the state in which the resin (polyphenylene sulfide) of the positive electrode resin member actually fills the gaps between the nanocolumns. [Figure 10] 4 is a flowchart of a method for manufacturing a battery according to an embodiment. [Figure 11] 1A is a schematic diagram showing the roughening treatment performed on the roughened region on the underside of the lid, and FIG. 1B is a schematic diagram showing the roughening treatment performed on the roughened region on the side of the terminal. [Figure 12] 1A to 1C are diagrams illustrating an insert molding process. [Figure 13] FIG. 2 is an explanatory diagram illustrating a test specimen. [Figure 14] 13 is a table showing the relationship between various conditions of pulsed laser irradiation performed on a roughened region and the average height and surface area ratio of nanocolumns formed in the roughened region. [Figure 15] (A) is a scatter plot in which the horizontal axis represents the average height of the nanocolumns and the vertical axis represents the amount of helium leakage, and (B) is a scatter plot in which the horizontal axis represents the surface area ratio and the vertical axis represents the amount of helium leakage. [Figure 16]16(A) is an example of a cross-sectional image of a cross-sectional sample obtained using a scanning electron microscope, and (B) is an explanatory diagram explaining the cross-sectional area and base length of a nanocolumn based on FIG. 16(A). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. The battery 1 constituting the metal-resin composite of the present invention is an example of an electricity storage device, specifically, a rectangular sealed lithium ion secondary battery mounted on vehicles such as hybrid cars, plug-in hybrid cars, and electric cars. In the following, the symbols X, Y, and Z relating to the directions in the drawings represent the left-right direction, the front-rear direction, and the up-down direction as specifying the direction. In addition, the symbols U, D, L, R, F, and B written at the end of the arrows relating to each direction represent the upper side, lower side, left side, right side, front side, and rear side as specifying the position. However, these directions and positions are specified for convenience of explanation. Therefore, the direction in which the battery 1 is installed is not limited in any way.
[0011] [Battery configuration] Fig. 1 is a perspective view of a battery 1. Fig. 2 is a cross-sectional view taken along line AA in Fig. 1. As shown in Figs. 1 and 2, the battery 1 has a case 10 that seals the inside, an electrode assembly 40 housed in the case 10, an electrolyte 3 and an insulating holder 5, and a positive electrode terminal member 50 and a negative electrode terminal member 60 connected to the electrode assembly 40.
[0012] Case 10 has an overall flat rectangular parallelepiped shape with a bottom. In this embodiment, case 10 is made of aluminum. However, the material of case 10 is not limited to aluminum, but is preferably made of metal. For example, case 10 may be made of other metals such as aluminum alloys, iron, and iron alloys. Case 10 is composed of a main body member 20 and a cover member 30.
[0013] The main body member 20 has a bottomed rectangular tube shape. The main body member 20 also has an opening 21. In other words, the main body member 20 has a rectangular plate-shaped bottom 12, a pair of front side parts 13 and rear side parts 14 that are vertically erected from the edge of the front side F and the edge of the rear side B of the bottom 12, and a pair of left side parts 15 and right side parts 16 that are vertically erected from the end of the left side L and the end of the right side R of the bottom 12. The shape of the opening 21 is a rectangle with the left-right direction X as the long side direction and the front-rear direction Y as the short side direction. The shape of the bottom 12 is a rectangular plate with the left-right direction X as the long side direction and the front-rear direction Y as the short side direction. The shape of the front side part 13 and the rear side part 14 is a rectangular plate with the left-right direction X as the long side direction and the up-down direction Z as the short side direction. The shape of the left side part 15 and the right side part 16 is a rectangular plate with the up-down direction Z as the long side direction and the up-down direction Y as the short side direction.
[0014] The height (length in the vertical direction Z) of the front portion 13 and the rear portion 14 is the same as the height (length in the vertical direction Z) of the left portion 15 and the right portion 16. Furthermore, the height (length in the vertical direction Z) of the front portion 13, etc. and the length in the horizontal direction X of the front portion 13 and the rear portion 14 are significantly longer than the length in the front-to-back direction Y of the left portion 15 and the right portion 16. Therefore, hereinafter, with regard to the case 10, the main body member 20 and the cover member 30, the horizontal direction X may be referred to as the "length direction", the front-to-back direction Y as the "width direction", and the vertical direction as the "height direction".
[0015] The lid member 30 closes the opening 21 of the main body member 20. In detail, the peripheral portion of the lid member 30 is laser welded over the entire circumference to the tip portions of the upper sides U of the front side portion 13, the rear side portion 14, the left side portion 15, and the right side portion 16. Note that at the boundary portion between the tip portion of the main body member 20 and the peripheral portion of the lid member 30, a melted and solidified portion 18 is formed over the entire circumference where the main body member 20 and the lid member 30 are melted and solidified by the laser.
[0016] A safety valve 19 is provided slightly to the left L of the center of the lid member 30 in the left-right direction X. The safety valve 19 breaks and opens when the internal pressure of the case 10 exceeds a valve opening pressure. A liquid inlet hole 30k that penetrates the lid member 30 in the up-down direction Z is formed slightly to the right R of the center of the lid member 30 in the left-right direction X. An aluminum sealing member 39 is fitted into the liquid inlet hole 30k from an upper side U, thereby airtightly sealing the liquid inlet hole 30k.
[0017] A positive electrode insertion hole 33h is formed near the end of the cover member 30 on one side in the left-right direction X (left side L in Figs. 1 and 2), penetrating the cover member 30 in the up-down direction Z. A negative electrode insertion hole 34h is formed near the end of the cover member 30 on the other side in the left-right direction X (right side R in Figs. 1 and 2), penetrating the cover member 30 in the up-down direction Z. The positive electrode insertion hole 33h and the negative electrode insertion hole 34h are formed in a rectangular shape with the left-right direction X as the long side direction and the front-rear direction Y as the short side direction. A positive electrode terminal member 50 having an overall vertically elongated shape (extending in one direction) is inserted from the upper side U along the length direction into the positive electrode insertion hole 33h. A negative electrode terminal member 60 having an overall vertically elongated shape (extending in one direction) is inserted from the upper side U along the length direction into the negative electrode insertion hole 34h.
[0018] The positive electrode terminal member 50 is fixed to the lid member 30 in a state insulated from the lid member 30 via the positive electrode resin member 70. Therefore, the positive electrode terminal member 50 is supported by the lid member 30 via the positive electrode resin member 70. In this embodiment, the positive electrode terminal member 50 is made of aluminum. However, the material of the positive electrode terminal member 50 can be appropriately set within a range that allows electrical connection with a positive electrode current collecting portion 41r of the electrode body 40 described later.
[0019] The negative electrode terminal member 60 is fixed to the lid member 30 in a state insulated from the lid member 30 via the negative electrode resin member 80. Therefore, the negative electrode terminal member 60 is supported by the lid member 30 via the negative electrode resin member 80. In this embodiment, the negative electrode terminal member 60 is made of copper. However, the material of the negative electrode terminal member 60 can be appropriately selected within a range that allows electrical connection with the negative electrode current collecting part 42r of the electrode body 40 described later.
[0020] The electrode body 40 is a so-called "wound type" electrode body. In the electrode body 40, a strip-shaped positive electrode plate 41 and a strip-shaped negative electrode plate 42 are wound in a predetermined winding direction with a strip-shaped separator 43 sandwiched therebetween. As a result, the electrode body 40 is formed in a flat shape having horizontally elongated rectangular side surfaces extending in the vertical direction Z and the horizontal direction X on the front side F and the rear side B as a whole.
[0021] The positive electrode plate 41 has a positive electrode current collecting foil (not shown) and a positive electrode active material layer (not shown) supported on the current collecting foil. The positive electrode current collecting foil is made of aluminum. However, the material of the positive electrode current collecting foil can be appropriately set within a range in which it can function as a positive electrode of a lithium ion secondary battery. On the other hand, the negative electrode plate 42 has a negative electrode current collecting foil (not shown) and a negative electrode active material layer (not shown) supported on the current collecting foil. The negative electrode current collecting foil is made of copper. However, the material of the negative electrode current collecting foil can be appropriately set within a range in which it can function as a negative electrode of a lithium ion secondary battery.
[0022] In addition, a positive electrode current collecting portion 41r is formed on the electrode body 40. The positive electrode current collecting portion 41r is a portion where the positive electrode current collecting foil is exposed. A positive electrode terminal lower portion 52 of the positive electrode terminal member 50 is bonded to the positive electrode current collecting portion 41r. Similarly, a negative electrode current collecting portion 42r is formed on the electrode body 40. The negative electrode current collecting portion 42r is a portion where the negative electrode current collecting foil is exposed. A negative electrode terminal lower portion 62 of the negative electrode terminal member 60 is bonded to the negative electrode current collecting portion 42r. Therefore, the electrode body 40 is supported by the cover member 30 via the positive electrode terminal member 50 and the negative electrode terminal member 60.
[0023] Although detailed illustration is omitted, the positive electrode current collecting portion 41r is a portion that protrudes beyond the negative electrode plate 42 and the separator 43 in the axial direction of the electrode body 40 and is wound with only the positive electrode current collecting foil. Similarly, the negative electrode current collecting portion 42r is a portion that protrudes beyond the positive electrode plate 41 and the separator 43 in the axial direction of the electrode body 40 and is wound with only the negative electrode current collecting foil. In this embodiment, the positive electrode current collecting portion 41r is formed at the end of the left side L of the electrode body 40. Moreover, the negative electrode current collecting portion 42r is formed at the end of the right side R of the electrode body 40.
[0024] The electrode body 40 is spaced apart from the bottom 12, front side 13, rear side 14, left side 15, right side 16, and cover member 30 of the main body member 20 by a certain distance. An insulating holder 5 is disposed between the electrode body 40 and the main body member 20 to reliably maintain insulation. The shape and material of the insulating holder 5 can be appropriately set as long as it can be disposed between the electrode body 40 and the main body member 20 and can insulate the electrode body 40 from the main body member 20. In this embodiment, the insulating holder 5 is made of a strip-shaped film of polypropylene (PP), which is a synthetic resin. The insulating holder 5 is formed in a bag shape. The bag-shaped insulating holder 5 encases the electrode body 40 with the upper side U open. That is, the insulating holder 5 insulates the inner surfaces of the bottom 12 , front side 13 , rear side 14 , left side 15 and right side 16 of the body member 20 from the outer surface of the electrode body 40 facing the body member 20 .
[0025] The positive electrode resin member 70 is made of a thermoplastic resin, specifically polyphenylene sulfide (PPS). The positive electrode resin member 70 is bonded to the cover member 30 and the positive electrode terminal member 50. The cover member 30, the positive electrode terminal member 50, and the positive electrode resin member 70 are integrated by bonding the positive electrode resin member 70 to the cover member 30 and the positive electrode terminal member 50, so that the battery 1 including the integrated member constitutes a composite body of metal and resin. The positive electrode resin member 70 also provides insulation between the cover member 30 and the positive electrode terminal member 50 and hermetically seals them. That is, the positive electrode resin member 70 functions as an insulating member and a sealing member between the cover member 30 and the positive electrode terminal member 50. The material of the positive electrode resin member 70 can be appropriately selected as long as it can hermetically seal the lid member 30 and the positive electrode terminal member 50 while insulating them from each other, and can also be other types of resin such as other types of thermoplastic resins or thermosetting resins.
[0026] The negative electrode resin member 80 is made of a thermoplastic resin, specifically polyphenylene sulfide (PPS). The negative electrode resin member 80 is bonded to the lid member 30 and the negative electrode terminal member 60. The lid member 30, the negative electrode terminal member 60, and the negative electrode resin member 80 are integrated by bonding the negative electrode resin member 80 to the lid member 30 and the negative electrode terminal member 60, so that the battery 1 including the integrated member constitutes a composite body of metal and resin. The negative electrode resin member 80 also provides insulation between the lid member 30 and the negative electrode terminal member 60 while hermetically sealing them. That is, the negative electrode resin member 80 functions as an insulating member and a sealing member between the lid member 30 and the negative electrode terminal member 60. The material of the negative electrode resin member 80 can be appropriately selected as long as it can hermetically seal the lid member 30 and the negative electrode terminal member 60 while insulating them from each other, and can also be other types of resin such as other types of thermoplastic resins or thermosetting resins.
[0027] Next, the shape of the positive electrode terminal member 50 will be described. Fig. 3 is a perspective view of the positive electrode terminal member 50. As shown in Fig. 3, the positive electrode terminal member 50 has a positive electrode terminal upper part 51, a positive electrode terminal lower part 52, and a positive electrode terminal intermediate part 53. In the battery 1, the positive electrode terminal upper part 51 is disposed relatively on the upper side U. The positive electrode terminal lower part 52 is disposed relatively on the lower side D.
[0028] The positive terminal upper part 51 has a constant L-shaped cross-sectional shape in one direction. In detail, one straight line portion of the L-shape is longer than the other straight line portion of the L-shape. Therefore, the rectangular plate-shaped portion of the positive terminal upper part 51 that corresponds to the longer straight line portion of the L-shaped cross-sectional shape is referred to as the "long straight line portion 51a," and the portion extending perpendicularly from one edge of the long straight line portion 51a is referred to as the "short straight line portion 51b."
[0029] In the following description of the positive electrode terminal member 50, for convenience, the symbols O, P, and Q shown in FIG. 3 are used to specify directions. The symbols O, P, and Q represent "the direction in which the L-shaped cross-sectional shape of the positive electrode terminal upper part 51 extends at a constant rate", "the direction along the long straight portion 51a of the L-shaped cross-sectional shape of the positive electrode terminal upper part 51", and "the direction along the short straight portion 51b of the L-shaped cross-sectional shape of the positive electrode terminal upper part 51", respectively. In the following description of the positive electrode terminal member 50, the side in which the positive electrode terminal upper part 51 is located in the third direction Q may be referred to as the "upper side", and the side in which the positive electrode terminal lower part 52 is located in the third direction Q may be referred to as the "lower side".
[0030] The positive terminal lower portion 52 is formed perpendicular to the long straight portion 51a as a whole. The positive terminal lower portion 52 is shaped like a rectangular plate with its long side in the third direction Q and its short side in the second direction P. In addition, in the first direction O, a part of the positive terminal lower portion 52 fits inside the positive terminal upper portion 51, and another part protrudes outside the positive terminal upper portion 51. In addition, in the second direction P, a part of the positive terminal lower portion 52 fits inside the positive terminal upper portion 51, and another part protrudes outside the positive terminal upper portion 51.
[0031] The positive terminal intermediate portion 53 has an overall crank shape, and connects the positive terminal upper portion 51 and the positive terminal lower portion 52. When viewed from the second direction P, the positive terminal intermediate portion 53 has a rectangular shape with its longer side in the first direction O and its shorter side in the third direction. The length of the positive terminal intermediate portion 53 in the first direction O is longer than the length of the positive terminal lower portion 52 in the first direction O. The side surface of the positive terminal lower portion 52 that protrudes outward from the positive terminal upper portion 51 in the first direction O is continuous with the side surface of the positive terminal intermediate portion 53 on the same side in the first direction O.
[0032] In addition, both surfaces of the positive terminal intermediate portion 53 perpendicular to the second direction P near the connection to the short straight portion 51b are formed on the same plane as both surfaces of the short straight portion 51b perpendicular to the second direction P. Hereinafter, the portion of the positive terminal intermediate portion 53 formed on the same plane as both surfaces of the short straight portion 51b perpendicular to the second direction P is referred to as the "upper connection portion 53a". The surface of the positive terminal upper portion 51 including the short straight portion 51b on the side where the positive terminal lower portion 52 is located in the second direction P is flush with the surface of the upper connection portion 53a on the same side. In addition, on the opposite side of the short straight portion 51b in the third direction Q of the upper connection portion 53a, a bent portion 53b is formed that is bent in a crank shape toward the outside of the positive terminal upper portion 51 along the second direction P.
[0033] In this embodiment, the shape of the negative electrode terminal member 60 is the same as that of the positive electrode terminal member 50. Therefore, a description using a perspective view of the negative electrode terminal member 60 will be omitted, but the negative electrode terminal member 60 has a negative electrode terminal upper portion 61, a negative electrode terminal lower portion 62, and a negative electrode terminal intermediate portion 63 corresponding to the positive electrode terminal upper portion 51, the positive electrode terminal lower portion 52, and the positive electrode terminal intermediate portion 53, similar to the positive electrode terminal member 50.
[0034] Next, the joint structure between the positive electrode resin member 70 and the lid member 30 and the positive electrode terminal member 50, and the roughening treatment of the lid member 30 and the positive electrode terminal member 50 will be described. FIG. 4 is a perspective view of a unit member 1A consisting of the lid member 30, the positive electrode terminal member 50, the positive electrode resin member 70, the negative electrode terminal member 60, and the negative electrode resin member 80, which are integrated and form a part of the battery 1 shown in FIG. 1 and FIG. 2. FIG. 5(A) is a BB cross-sectional view of FIG. 4, and FIG. 5(B) is a CC cross-sectional view of FIG. 4. FIG. 6 is an explanatory diagram for explaining the joint region between the lid member 30 and the positive electrode resin member 70, and the region of the lid member 30 that has been roughened. FIG. 7 is an explanatory diagram for explaining the joint region between the positive electrode terminal member 50 and the positive electrode resin member 70, and the region of the positive electrode terminal member 50 that has been roughened.
[0035] The positive electrode terminal member 50 is fixed to the lid member 30 via the positive electrode resin member 70 with the first direction O parallel to the left-right direction X and the positive electrode terminal lower portion 52 disposed on the rear side B. On the other hand, the negative electrode terminal member 60 is fixed to the lid member 30 via the negative electrode resin member 80 with the first direction O parallel to the left-right direction X and the negative electrode terminal lower portion 62 disposed on the front side F.
[0036] The top surface of the long straight portion 51a is exposed to the upper side U. In addition, the top surface of the cover member 30 and the bottom surface of the long straight portion 51a are disposed at substantially the same position in the vertical direction Z. Furthermore, the bottom surface of the short straight portion 51b is disposed at a position slightly lower than the bottom surface of the cover member 30 in the vertical direction Z. In a plan view (a line of sight from the upper side U to the lower side D), the long straight portion 51a of the positive electrode terminal member 50 inserted into the positive electrode insertion hole 33h is completely contained within the positive electrode insertion hole 33h. In the left-right direction X and the front-rear direction Y, the long straight portion 51a is disposed at substantially the center of the positive electrode insertion hole 33h.
[0037] The positive electrode resin member 70 is formed in the vertical direction Z from the upper end of the positive electrode terminal upper part 51 to a position slightly above the lower end of the upper connection part 53a. The positive electrode resin member 70 hermetically seals the gap between the cover member 30 and the positive electrode terminal member 50. As described later, in this embodiment, the positive electrode resin member 70 is integrally formed by insert molding. For convenience, the portion of the positive electrode resin member 70 above the upper surface of the cover member 30 is referred to as the "positive electrode resin upper part 71", the portion below the lower surface of the cover member 30 is referred to as the "positive electrode resin lower part 72", and the portion between the upper and lower surfaces of the cover member 30, in other words, the portion filled in the positive electrode insertion hole 33h, is referred to as the "positive electrode resin middle part 73".
[0038] The positive electrode resin upper portion 71 has a positive electrode resin upper frame portion 71a that surrounds the entire periphery of the long straight portion 51a, and a positive electrode resin upper protrusion portion 71b that is connected to the positive electrode resin upper frame portion 71a.
[0039] The positive resin upper frame portion 71a is formed in a rectangular frame shape. The first width W1, which is the distance from the inner edge to the outer edge of each straight portion of the positive resin upper frame portion 71a, is approximately the same. The positive resin upper protrusion portion 71b is formed to protrude toward the right side R from a part of the range of approximately the center of the straight portion formed on the right side R of the positive resin upper frame portion 71a. The shape of the positive resin upper protrusion portion 71b is a rectangular plate shape with the left-right direction X as the long side direction and the front-rear direction Y as the short side direction. The length of the positive resin upper protrusion portion 71b in the left-right direction X and the length of the front-rear direction Y are longer than the first width W1. The positive resin upper protrusion portion 71b is a portion where a gate member GT (see FIG. 12) into which molten resin is injected during the insert molding is placed.
[0040] The positive electrode resin upper frame portion 71a is joined to the entire outer surface of the long straight portion 51a and to a rectangular annular lid upper frame joining region E11 that surrounds the entire edge of the positive electrode insertion hole 33h on the upper surface of the lid member 30. A second width W2, which is the distance from the inner edge to the outer edge of each straight portion of the lid upper frame joining region E11, is approximately the same. The positive electrode resin upper protrusion 71b is joined to the upper surface of the lid member 30 over the entire bottom surface.
[0041] In the following, the region on the upper surface of the lid member 30 that is joined to the positive electrode resin upper protrusion 71b is referred to as the "lid upper surface rectangular joining region E12". The lid upper surface rectangular joining region E12 is formed by protruding toward the right side R from a part of the range of approximately the center of the straight part on the right side R of the lid upper surface frame-shaped joining region E11. That is, the lid upper surface frame-shaped joining region E11 and the lid upper surface rectangular joining region E12 are connected to each other and constitute a joining region with the positive electrode resin member 70 on the upper surface of the lid member 30. Therefore, the lid upper surface frame-shaped joining region E11 and the lid upper surface rectangular joining region E12 are collectively referred to as the "lid upper surface joining region E1".
[0042] The positive electrode resin lower portion 72 is generally formed in a rectangular plate shape with its long sides in the left-right direction X and its short sides in the front-rear direction Y. The overlapping portions of the positive electrode terminal member 50 in the up-down direction Z are completely embedded inside the positive electrode resin lower portion 72. Therefore, the positive electrode resin lower portion 72 is joined to the entire outer surfaces of the overlapping portions of the short straight portion 51b and the upper connection portion 53a of the positive electrode terminal member 50 in the up-down direction Z.
[0043] The positive electrode resin lower portion 72 is joined to a rectangular annular lid underside joining region E2 that completely surrounds the edge of the positive electrode insertion hole 33h on the underside of the lid member 30. The distances from the inner edge to the outer edge of each straight portion of the lid underside joining region E2 are substantially the same on the front side F and the rear side B and are substantially the same on the left side L and the right side R. A fourth width W4, which is the distance from the inner edge to the outer edge of the straight portion on the left side L and the right side R, is wider than a third width W3, which is the distance from the inner edge to the outer edge of the straight portion on the front side F and the rear side B.
[0044] The positive electrode resin intermediate portion 73 is connected to the positive electrode resin upper portion 71 and the positive electrode resin lower portion 72. The positive electrode resin intermediate portion 73 is filled in the positive electrode insertion hole 33h. Therefore, the positive electrode resin intermediate portion 73 is joined to the inner surface of the positive electrode insertion hole 33h of the cover member 30 over the entire circumference. Furthermore, the portion of the short straight portion 51b of the positive electrode terminal member 50 that overlaps in the vertical direction Z is completely embedded inside the positive electrode resin intermediate portion 73. Therefore, the positive electrode resin intermediate portion 73 is joined to the entire outer surface of the portion of the short straight portion 51b of the positive electrode terminal member 50 that overlaps in the vertical direction Z.
[0045] The entire outer surface of the long straight portion 51a of the positive terminal member 50 is joined to the positive resin upper frame portion 71a. The entire outer surface of the short straight portion 51b of the positive terminal member 50 overlapping with the positive resin intermediate portion 73 and the positive resin lower portion 72 in the vertical direction Z is joined to the positive resin intermediate portion 73 and the positive resin lower portion 72. The entire outer surface of the upper connection portion 53a of the positive terminal member 50 overlapping with the positive resin lower portion 72 in the vertical direction Z is joined to the positive resin intermediate portion 73 and the positive resin lower portion 72. Therefore, the region of the side surface of the positive terminal member 50 that is flush across the positive terminal upper portion 51 and the upper connection portion 53a and that is joined to the positive resin member 70 is referred to as the "terminal side surface joining region E3." In addition, the area that is joined to the positive electrode resin member 70, which is the entire lower surface of the long straight portion 51a on the side of the positive electrode terminal member 50 in the third direction Q on which the positive electrode terminal lower portion 52 is formed, is referred to as the "terminal lower surface joining area E4."
[0046] Thus, the cover member 30 and the positive electrode terminal member 50 have a plurality of bonding regions with the positive electrode resin member 70. Then, in order to improve the sealing performance, specific regions of the cover member 30 and the positive electrode terminal member 50, including the bonding regions with the positive electrode resin member 70, are subjected to a roughening treatment by pulse laser irradiation. The roughening treatment will now be described.
[0047] Roughening treatment is applied to a lid upper surface roughened region F1 that completely surrounds and contains inside the lid upper surface joining region E1 on the upper surface of the lid member 30, and a lid lower surface roughened region F2 that completely surrounds and contains inside the lid lower surface joining region E2 on the lower surface of the lid member 30. Furthermore, roughening treatment is applied to a terminal side surface roughened region F3 that completely surrounds and contains inside the terminal side surface joining region E3 by the entire side surface that is flush across the positive terminal upper portion 51 and the upper connection portion 53a of the positive terminal member 50, and a terminal lower surface roughened region F4 which is the terminal lower surface joining region E4 itself.
[0048] Although detailed conditions will be described later, the roughening treatment of the roughened lid upper surface region F1, the roughened lid lower surface region F2, the roughened terminal side surface region F3, and the roughened terminal lower surface region F4 is performed by pulsed laser irradiation. In the roughened lid upper surface region F1 and the roughened lid lower surface region F2, a base layer 35 formed by debris particles being deposited in a planar shape, and a column group layer 36 in which a large number of nano-columns 361, in which debris particles are linked together in a string of beads and extend in the height direction, stand in a two-dimensional forest, are laminated. Similarly, in the roughened terminal side surface region F3 and the roughened terminal lower surface region F4, a base layer 55 formed by debris particles being deposited in a planar shape, and a column group layer 56 in which a large number of nano-columns 561, in which debris particles are linked together in a string of beads and extend in the height direction, stand in a two-dimensional forest, are laminated. That is, the lid upper surface bonding region E1 and the lid lower surface bonding region E2, which are bonded to the positive electrode resin member 70 and seal the space between the outside and inside of the battery 1 together with the positive electrode resin member 70, include a basic layer 35 formed by a planar accumulation of debris particles on the surface of the lid member 30, and a column group layer 36 in which debris particles are linked to the basic layer 35 in a string-like pattern and nanocolumns 361 extending in the height direction are arranged in a two-dimensional forest. Similarly, the terminal side surface bonding region E3 and terminal underside bonding region E4, which are bonded to the positive electrode resin member 70 and seal the space between the outside and inside of the battery 1 together with the positive electrode resin member 70, include a terminal side surface roughened region F3 and a terminal underside roughened region F4, which are formed with a basic layer 55 formed by a planar accumulation of debris particles on the surface of the positive electrode terminal member 50, and a column group layer 56 in which debris particles are linked to the basic layer 55 in a string-like pattern and nanocolumns 561 extending in the height direction are arranged in a two-dimensional forest.
[0049] Debris particles are particles with a diameter of 100 nm or less that are formed when the surface of a metal component is irradiated with a pulsed laser, causing part of the surface to explosively evaporate, and then condense into compounds resulting from reactions between metal vapor or metal atoms and atmospheric gas. These particles then fall onto the surface near the laser irradiation position.
[0050] The average height of the numerous nanocolumns 361 standing in a forest of column layer 36 in each of the lid upper surface roughened region F1 and the lid lower surface roughened region F2, and the average height of the numerous nanocolumns 561 standing in a forest of column layer 56 in each of the terminal side surface roughened region F3 and the terminal lower surface roughened region F4, are 84 nm or more and less than 1000 nm.
[0051] The average surface area ratio of each of roughened region F1 on the lid upper surface, roughened region F2 on the lid lower surface, roughened region F3 on the terminal side surface, and roughened region F4 on the terminal lower surface is 12.9 or more. The surface area ratio here refers to the value obtained by dividing the geometric surface area of each of roughened regions F1 to F4 by the true surface area (true surface area) taking into account the unevenness including nanocolumns 361, 561 of each of roughened regions F1 to F4.
[0052] Here, an image showing the state in which the metal members (the cover member 30, the positive electrode terminal member 50) are actually roughened by pulsed laser irradiation, and the base layer (base layer 35, 55) and the column layer (column layer 36, 56) are formed is shown in FIG. 8. As shown in FIG. 8, the base layer (base layer 35, 55) formed by the accumulation of debris particles is laminated on the surface of the metal member (the cover member 30, the positive electrode terminal member 50). Furthermore, the base layer (base layer 35, 55) is laminated with a column layer (column layer 36, 56) in which a large number of nanocolumns (nanocolumns 361, 561) in which debris particles are linked together in a string and extend in the height direction stand two-dimensionally. Note that one interval of the scale written in the lower right corner of the image in FIG. 8 represents 30 nm.
[0053] In the battery 1, the resin (polyphenylene sulfide) of the positive electrode resin member 70 fills the gaps between the nanocolumns 361, 561 in a state where it reaches the base layers 35, 55. In other words, the positive electrode resin member 70 is bonded to the surfaces of the nanocolumns 361, 561 and the surfaces of the base layers 35, 55. FIG. 9 shows an image showing how the resin (polyphenylene sulfide) of the positive electrode resin member 70 actually fills the gaps between a large number of nanocolumns (nanocolumns 361, 561). Note that one interval of the scale written in the lower right corner of the image on the left side of FIG. 9 represents 10 μm, and one interval of the scale written in the lower right corner of the image on the right side of FIG. 9 represents 15 nm.
[0054] The joint structure between the negative electrode resin member 80 and the lid member 30 and the negative electrode terminal member 60 is configured similarly to the joint structure between the positive electrode resin member 70 and the lid member 30 and the positive electrode terminal member 50 described above with reference to Figures 5 to 9. The roughening treatment of the joint region between the lid member 30 and the negative electrode resin member 80 and the joint region between the negative electrode terminal member 60 and the negative electrode resin member 80 is configured similarly to the roughening treatment of the lid member 30 and the positive electrode terminal member 50 described above with reference to Figures 5 to 9.
[0055] [Battery manufacturing] Next, a manufacturing method of the battery 1 will be described with reference to the flowchart of Fig. 10. The manufacturing method of the battery 1 includes a member preparation step S1, a laser irradiation step S2, an insert molding step S3, a lid assembly completion step S4, a closing step S5, a welding step S6, a liquid injection / sealing step S7, and an initial charging / aging step S8.
[0056] In the member preparation step S1, the cover member 30, the positive electrode terminal member 50, and the negative electrode terminal member 60 are prepared. Specifically, the liquid injection hole 30k, the positive electrode insertion hole 33h, the negative electrode insertion hole 34h, and the safety valve 19 are formed in an aluminum plate by a conventional general processing method to obtain the cover member 30. In addition, the positive electrode terminal member 50 having the shape shown in FIG. 3 is obtained from the aluminum plate by a conventional general processing method. Furthermore, the negative electrode terminal member 60 having the same shape as the positive electrode terminal member 50 is obtained from a copper plate by a conventional general processing method.
[0057] Following the member preparation step S1, a laser irradiation step S2 is performed. In the laser irradiation step S2, a roughening treatment is performed by irradiating a pulsed laser on the surface of the lid member 30 that may become the lid upper surface roughened region F1 and the lid lower surface roughened region F2 in a state where the base layer 35 and the column group layer 36 are not formed, so that debris particles derived from the lid member 30 are deposited and grown into a large number of nano-columns 361 to form the lid upper surface roughened region F1 and the lid lower surface roughened region F2. Similarly, in the laser irradiation step S2, a roughening treatment is performed by irradiating a pulsed laser on the surface of the positive electrode terminal member 50 that may become the terminal side surface roughened region F3 and the terminal lower surface roughened region F4 in a state where the base layer 55 and the column group layer 56 are not formed, so that debris particles derived from the positive electrode terminal member 50 are deposited and grown into a large number of nano-columns 561 to form the terminal side surface roughened region F3 and the terminal lower surface roughened region F4.
[0058] As an example of various conditions of the pulsed laser irradiation in the laser irradiation step S2, the energy density of one pulse of laser irradiation is 24 J / cm for aluminum. 2 , and 32 J / cm for copper. 2 For example, for aluminum, the wavelength is set to 1060 nm, the average power to 25 W, the pulse period to 40 μs, the pulse width to 50 ns, the spot diameter to 63 μm, the feed rate to 1450 mm / s, and the line pitch to 0.059 mm. Figure 11 is a schematic diagram showing the trajectory of pulse laser irradiation when the pulse laser is irradiated to the lid undersurface roughened region F2 and the terminal side surface roughened region F3 in the laser irradiation step S2.
[0059] As shown in FIG. 11(A), the lid underside roughened region F2 is irradiated with a pulsed laser at the tip (the side marked "start point" in FIG. 11(A)) of one side (the left side L in FIG. 11(A)) along the left-right direction X in the lid underside roughened region F2, proceeding to one side in the front-rear direction Y (the rear side B in FIG. 11(A)). Next, the pulsed laser is irradiated by shifting the other side (the right side R in FIG. 11(A)) along the left-right direction X by the set line pitch (0.059 mm) and proceeding to the other side (the front side F in FIG. 11(A)) along the front-rear direction Y. Then, the pulsed laser is irradiated by shifting the other side (the right side R in FIG. 11(A)) along the left-right direction X by the set line pitch (0.059 mm) and proceeding again to the rear side B in FIG. 11(A). Thereafter, the pulsed laser irradiation is repeated to travel to one side or the other of the front-to-back direction Y until it reaches the tip (the side marked "end point" in FIG. 11(A)) of the other side (the right side R in FIG. 11(A)) along the left-right direction X in the lid undersurface roughened region F2.
[0060] In this way, the lid underside roughened region F2 is irradiated with a pulsed laser to form a base layer 35 and a column group layer 36. First, the debris particles of the lid member 30 are attached to the surface of the lid member 30 in a scattered manner, forming a planar base layer 35. Next, as the scattered attachment of the debris particles progresses, the debris particles are bonded to the base layer 35, and a large number of short protruding nanocolumns 361 extending in the height direction stand in a two-dimensional forest. As the scattered attachment of the debris particles progresses further, the debris particles are bonded to the base layer 35 in a string of beads, and a large number of long columnar nanocolumns 361 extending in the height direction stand in a two-dimensional forest. For example, nanocolumns 361 with a high average height can be formed by increasing the energy density of the pulsed laser irradiation.
[0061] In addition, the position where pulsed laser irradiation starts for the roughened lid undersurface region F2 (the side marked "start point" in FIG. 11(A)) is not limited to FIG. 11(A), and the side marked "end point" in FIG. 11(A) may be the position where pulsed laser irradiation starts. In addition, pulsed laser irradiation for the roughened lid upper surface region F1 is also performed in the same manner as pulsed laser irradiation for the roughened lid lower surface region F2 shown in FIG. 11(A). However, pulsed laser irradiation for the roughened lid upper surface region F1 and pulsed laser irradiation for the roughened lid lower surface region F2 may be performed in different manners.
[0062] As shown in FIG. 11B, the terminal side roughened region F3 is irradiated with a pulsed laser beam traveling in one of the second directions P of the positive terminal member 50 at the tip of one side of the terminal side roughened region F3 along the third direction Q of the positive terminal member 50 (the side marked "start point" in FIG. 11B). Next, the pulsed laser beam is shifted to the other side of the positive terminal member 50 along the third direction Q by the set line pitch (0.059 mm) and travels in the other of the second directions P. Then, the pulsed laser beam is shifted to the other side of the positive terminal member 50 along the third direction Q by the set line pitch (0.059 mm) and travels in one of the second directions P again. Thereafter, the pulsed laser beam irradiation traveling in one or the other of the second directions P is repeated until the pulsed laser beam irradiation traveling in the other side of the terminal side roughened region F3 along the third direction Q (the side marked "end point" in FIG. 11B) is reached.
[0063] In this way, the base layer 55 and the column group layer 56 are formed by irradiating the terminal side roughened region F3 with a pulsed laser. First, the debris particles of the positive electrode terminal member 50 are attached in a scattered manner to the surface of the positive electrode terminal member 50, forming a planar base layer 55. Next, as the scattered attachment of the debris particles progresses, the debris particles are bonded to the base layer 55, and a large number of short protruding nanocolumns 561 extending in the height direction stand in a two-dimensional forest. As the scattered attachment of the debris particles progresses further, the debris particles are bonded to the base layer 55 in a string of beads, and a large number of long columnar nanocolumns 561 extending in the height direction stand in a two-dimensional forest. For example, by increasing the energy density of the pulsed laser irradiation, nanocolumns 561 with a high average height can be formed.
[0064] In addition, the position where the pulsed laser irradiation is started for the rough terminal side surface region F3 (the side marked "start point" in FIG. 11(B)) is not limited to FIG. 11(B), and the side marked "end point" in FIG. 11(B) may be the position where the pulsed laser irradiation is started. The pulsed laser irradiation for the rough terminal lower surface region F4 is also performed in the same manner as the pulsed laser irradiation for the rough terminal side surface region F3 shown in FIG. 11(B). However, in this case, the direction in which the pulsed laser irradiation proceeds is the same as the laser irradiation for the rough terminal side surface region F3, but the start position and end position of the pulsed laser irradiation are the tip on one side and the tip on the other side of the rough terminal lower surface region F4 along the second direction P of the positive electrode terminal member 50. Furthermore, the direction in which the pulsed laser irradiation is shifted by the set line pitch (0.059 mm) is one of the second directions P of the positive electrode terminal member 50.
[0065] In the laser irradiation step S2, the joining region of the lid member 30 with the negative electrode resin member 80 around the negative electrode insertion hole 34h is irradiated with a pulsed laser in substantially the same manner as the roughened lid upper surface region F1 and the roughened lid lower surface region F2. Similarly, the joining region of the negative electrode terminal member 60 with the negative electrode resin member 80 is irradiated with a pulsed laser in substantially the same manner as the roughened terminal side surface region F3 and the roughened terminal lower surface region F4. Here, "substantially the same manner" refers to the region to be irradiated with the pulsed laser and the conditions for the pulsed laser irradiation.
[0066] Following the laser irradiation step S2, an insert molding step S3 is performed. In the insert molding step S3, a positive electrode resin member 70 and a negative electrode resin member 80 are formed, and the positive electrode resin member 70 is joined to the lid member 30 and the positive electrode terminal member 50 to be integrated, and the negative electrode resin member 80 is joined to the lid member 30 and the negative electrode terminal member 60 to be integrated. That is, a unit member 1A that is a metal-resin composite is manufactured. FIG. 12 is an explanatory diagram that shows a schematic representation of the insert molding step S3 on the positive electrode terminal member 50 side.
[0067] In the insert molding step S3, a mold DE is used. The mold DE has a lower mold DE1 arranged on the lower side and an upper mold DE2 arranged on the upper side. First, the lower mold DE1 and the upper mold DE2 are set to place the cover member 30, the positive electrode terminal member 50, and the negative electrode terminal member 60 in predetermined positions. At this time, the positive electrode terminal member 50 inserted in the positive electrode insertion hole 33h, the negative electrode terminal member 60 inserted in the negative electrode insertion hole 34h, and the cover member 30 are integrally supported by the mold DE. In addition, a space corresponding to the positive electrode resin member 70 and the negative electrode resin member 80 is formed by the set lower mold DE1 and upper mold DE2.
[0068] In the insert molding process S3, first, a filling process S31 is performed, and then a solidification process S32 is performed. In the filling process S31, as shown in FIG. 12, the molten resin MR, which is the material of the positive electrode resin member 70 and the negative electrode resin member 80, is injected from the gate member GT through the upper mold DE2 into the space formed by the lower mold DE1 and the upper mold DE2. At this time, for example, the molten resin MR fills the gaps between the numerous nanocolumns 361 constituting the column group layer 36 until it reaches the base layer 35. Similarly, the molten resin MR fills the gaps between the numerous nanocolumns 561 constituting the column group layer 56 until it reaches the base layer 55.
[0069] The material of the positive electrode resin member 70 and the negative electrode resin member 80 is mainly composed of polyphenylene sulfide, and contains a glass filler. The linear expansion coefficient of the material of the positive electrode resin member 70 and the negative electrode resin member 80 is set between the linear expansion coefficient of copper (1.65) and the linear expansion coefficient of aluminum (2.31).
[0070] After the injection of the molten resin MR is completed, the molten resin MR is appropriately cooled in the solidification step S32 to form the positive electrode resin member 70 and the negative electrode resin member 80. In detail, for example, the molten resin MR filled in the gaps between the numerous nanocolumns 361 in the filling step S31 until it reaches the base layer 35, and the molten resin MR filled in the gaps between the numerous nanocolumns 561 until it reaches the base layer 55 is solidified to form the positive electrode resin member 70 bonded to the bonding regions E1 to E4 including the roughened regions F1 to F4. Similarly, the negative electrode resin member 80 is also formed. Then, the upper mold DE2 is moved upward, and the unit member 1A consisting of the integrated lid member 30, the positive electrode resin member 70, the positive electrode terminal member 50, the negative electrode resin member 80, and the negative electrode terminal member 60 is taken out from the lower mold DE1.
[0071] After the insert molding step S3, a lid assembly completion step S4 is performed. In the lid assembly completion step S4, the lid assembly is completed. Specifically, the electrode body 40 is prepared, and the positive electrode terminal lower part 52 and the negative electrode terminal lower part 62 of the unit member 1A generated in the insert molding step S3 are welded and connected to the positive electrode current collecting part 41r and the negative electrode current collecting part 42r of the electrode body 40, respectively. Thereafter, the electrode body 40 in this state is wrapped in a bag-shaped insulating holder 5. As a result, a lid assembly consisting of the lid member 30, the positive electrode terminal member 50, the negative electrode terminal member 60, the positive electrode resin member 70, the negative electrode resin member 80, the electrode body 40, and the insulating holder 5 is completed.
[0072] Following the lid assembly completion step S4, a closing step S5 is performed. In the closing step S5, a main body member 20 is prepared, and the portion of the lid assembly completed in the lid assembly completion step S4 below the lid member 30, including the electrode body 40 and the insulating holder 5, is inserted into the main body member 20, and the opening 21 of the main body member 20 is closed with the lid member 30.
[0073] Following the closing step S5, a welding step S6 is performed. In the welding step S6, the leading ends of the front side portion 13, the rear side portion 14, the left side portion 15, and the right side portion 16 of the main body member 20 are laser-welded to the peripheral edge portion of the cover member 30 along the entire periphery, thereby hermetically sealing the opening 21.
[0074] Following the welding step S6, a liquid injection / sealing step S7 is performed. In the liquid injection / sealing step S7, the electrolyte 3 is injected into the case 10 through the liquid injection hole 30k, and the electrolyte 3 is impregnated into the electrode body 40. Thereafter, the sealing member 39 is fitted into the liquid injection hole 30k from the upper side U, and the sealing member 39 is welded to the lid member 30 around its entire periphery to hermetically seal the gap between the sealing member 39 and the lid member 30.
[0075] Following the liquid injection and sealing step S7, a charging and aging step S8 is performed. In the charging and aging step S8, a charging device (not shown) is connected to the battery 1 to initially charge the battery 1. The initially charged battery 1 is then left for a predetermined period of time to age the battery 1. In this manner, the battery 1 is completed.
[0076] Next, an experiment for verifying the sealing property of the joint between the metal member and the resin member will be described. The experiment was conducted by the applicant. The experiment is referred to as the "sealing property verification experiment." The sealing property verification experiment is composed of the following three steps (1) to (3). (1) Production of test specimens (2) Liquid bath thermal shock test (3) Helium leak test
[0077] First, (1) the production of the test specimen will be described. The test specimen is a specimen for a sealing property verification experiment. FIG. 13 is an explanatory diagram that shows a schematic representation of the test specimen. In detail, FIG. 13(A) is a plan view of the test specimen, and FIG. 13(B) is a DD cross-sectional view of FIG. 13(A). The test specimen is formed by joining a plate-shaped metal member and a resin member. The plate-shaped metal member is made of aluminum or copper. That is, the test specimens include one in which the plate-shaped metal member is made of aluminum, and one in which the plate-shaped metal member is made of copper. The resin member is made of only one type of polyphenylene sulfide (PPS).
[0078] Regardless of the type of metal member, the plate-like metal member is generally formed in a square shape. A ventilation hole is formed at the center of the metal member in a plan view so as to penetrate the metal member in the thickness direction.
[0079] A roughened area is formed on the surface of the metal member that is bonded to the resin member. The roughened area is in the shape of a ring that surrounds the edge of the air hole with a substantially constant width. In the roughened area, a base layer and a column group layer are laminated by pulsed laser irradiation, as in the above-mentioned roughened areas F1 to F4. However, in the sealability verification experiment, multiple test specimens were prepared, and pulsed laser irradiation was performed under different conditions for each test specimen. Therefore, the average height and surface area ratio of the nanocolumns also differ depending on the test specimen. Figure 14 is a table showing the relationship between various conditions of pulsed laser irradiation performed on the roughened area and the average height and surface area ratio of the nanocolumns formed in the roughened area. In the sealability verification experiment, seven metal members made of aluminum and seven metal members made of copper were prepared.
[0080] Then, the resin member is joined to each metal member by insert molding. The resin member is shaped like a circular plate. The central axis of the resin member and the central axis of the vent hole are approximately the same. Therefore, in this experiment, the joint area between the resin member and the metal member coincides with the roughened area of the metal member. Moreover, the resin member is joined to the roughened area around the vent hole over the entire circumference while completely covering the vent hole. That is, in this experiment, the joint between the resin member and the metal member seals the space (first space) on the side of the metal member constituting the test specimen that is joined to the resin member and the space (second space) on the side that is not joined to the resin member.
[0081] Next, (2) Liquid bath thermal shock test will be described. A liquid bath thermal shock test was performed on each test specimen using a commercially available liquid bath thermal shock device (ES-96EXH-LS, Hitachi Appliances, Inc.).
[0082] Finally, (3) helium leak test is described. A known helium leak test was performed on each test specimen that had been subjected to the liquid bath thermal shock test, using a commercially available helium leak detector (HELiOT900, ULVAC, Inc.).
[0083] (3) The results of the helium leak test are shown in FIG. 15. FIG. 15(A) is a scatter plot in which the horizontal axis represents the average height of the nanocolumns and the vertical axis represents the amount of helium leak, and FIG. 15(B) is a scatter plot in which the horizontal axis represents the surface area ratio and the vertical axis represents the amount of helium leak. The vertical axes of FIG. 15(A) and FIG. 15(B) indicate that the amount of helium leak decreases toward the top. As shown in FIG. 15, the results of the sealability verification experiment showed that if the average height of the nanocolumns was 84 nm or more or the surface area ratio was 12.9 or more, the sealability of the joint between the metal member and the resin member was good.
[0084] Here, a method for calculating the average height of the nanocolumns in each roughened region in the sealability verification experiment will be described. In this calculation method, first, a plate-shaped metal member is prepared as a test piece. This metal member test piece is called the "average height test piece." Then, one entire plane of each average height test piece is irradiated with a pulsed laser under various conditions.
[0085] Next, a cross-sectional sample including the flat portion irradiated with the pulsed laser is prepared from each average height test piece using a predetermined cross-sectional sample preparation device (e.g., Cross Section Polisher (registered trademark): manufactured by JEOL Ltd.). The cross-sectional sample is parallel to the thickness direction of the average height test piece. Next, a cross-sectional image of each cross-sectional sample is obtained using a scanning electron microscope (S-4800, Hitachi High-Technologies Corporation). The magnification of this cross-sectional image is 150,000 times.
[0086] Next, the cross-sectional area and base length of the nanocolumns in each cross-sectional image are measured using known image processing software, and the height of the nanocolumns is calculated using the following mathematical formula 1.
number
[0087] Fig. 16(A) is an example of a cross-sectional image obtained using a scanning electron microscope, and Fig. 16(B) is an explanatory diagram for explaining the cross-sectional area and basal length of a nanocolumn based on Fig. 16(A). As shown in Fig. 16(B), the length of the curved portion is the basal length, and the total area of the standing nanocolumns is the cross-sectional area of the nanocolumn. Note that one interval of the scale indicated in the lower right corner of the images in Fig. 16(A) and Fig. 16(B) represents 30 nm.
[0088] Next, a method for calculating the surface area ratio of each roughened region in a sealability verification experiment will be described. In this calculation method, first, a plate-shaped metal member is prepared as a test piece. This metal member test piece is referred to as a "surface area ratio test piece." Then, a pulsed laser is irradiated under various conditions onto one plane of each surface area ratio test piece. In this experiment, the target of the pulsed laser irradiation is one of the planes. Next, the specific surface area of the surface area ratio test piece that has been irradiated with the pulsed laser is measured by a general krypton gas adsorption method.
[0089] Next, based on the measured specific surface area of the test piece for surface area ratio, the roughened surface area of the plane irradiated with the pulsed laser in the test piece for surface area ratio is calculated. The roughened surface area is calculated by the following Equation 2.
number
[0090] Furthermore, based on the calculated roughened surface area of the surface area ratio test piece, the surface area ratio of the plane irradiated with the pulsed laser in the surface area ratio test piece is calculated. The surface area ratio is calculated by the following Equation 3.
number
[0091] As described above, according to the lid member 30 having the bonding regions E1, E2, in which the positive electrode resin member 70 is bonded to the member surface and which seals the space between the first space that is the outside of the battery 1 and the second space that is the inside of the battery 1, the bonding regions E1, E2 include roughened regions F1, F2 formed on the member surface of the lid member 30 and including a basic layer 35 formed by the accumulation of debris particles and a column group layer 36 in which nanocolumns 361 extending in the height direction are two-dimensionally forested, with the debris particles being linked to the basic layer 35 in a string-like manner, and the forest of nanocolumns 361 having an average height of 84 nm or more, the sealing property of the bonding surface with the positive electrode resin member 70 can be improved compared to, for example, a metal member having protruding portions that cannot be considered columnar portions. Similarly, in the case of a positive electrode terminal member 50 having bonding regions E3, E4, the bonding regions E3, E4 include roughened regions F3, F4 formed on the surface of the positive electrode terminal member 50 and including a base layer 55 formed by the accumulation of debris particles and a column group layer 56 formed in a two-dimensional forest of nanocolumns 561 extending in the height direction and formed by debris particles being linked to the base layer 55 in a string-like pattern, and the forest of nanocolumns 561 has an average height of 84 nm or more, thereby improving the sealing property of the bonding surface with the positive electrode resin member 70 compared to, for example, a metal member formed with protruding portions that cannot be considered columnar portions.
[0092] In addition, the bonding regions E1, E2 are formed in a ring shape so as to surround the entire edge of the positive electrode insertion hole 33h, and the roughened regions F1, F2 are formed in a ring shape in the bonding regions E1, E2 so as to follow the shape of the bonding regions E1, E2. This improves the sealing ability of the positive electrode insertion hole 33h when the bonding regions E1, E2 are bonded to the positive electrode resin member 70.
[0093] Furthermore, the resin forming the positive electrode resin member 70 bonded to the bonding regions E1 and E2 fills the gaps between the nanocolumns 361 while reaching the base layer 35, improving the sealing performance of the bonded portion between the cover member 30 and the positive electrode resin member 70. Similarly, the resin forming the positive electrode resin member 70 bonded to the bonding regions E3 and E4 fills the gaps between the nanocolumns 561 while reaching the base layer 55, improving the sealing performance of the bonded surface between the positive electrode terminal member 50 and the positive electrode resin member 70.
[0094] In addition, the manufacturing method of the lid member 30 as a metal member includes a laser irradiation step S2 in which aluminum-derived debris particles, which are the material of the lid member 30, generated by pulse laser irradiation are deposited on the surface of the lid member 30 that can become the roughened regions F1 and F2 in a state where the base layer 35 and the column group layer 36 are not formed, and the aluminum-derived debris particles, which are the material of the lid member 30, are grown into nanocolumns 361 to form the roughened regions F1 and F2, thereby forming a bristling of nanocolumns 361 of 84 nm or more, and a lid member 30 with high sealing properties can be obtained. Similarly, the manufacturing method of the positive electrode terminal member 50 includes a laser irradiation step S2 in which aluminum-derived debris particles, which are the material of the positive electrode terminal member 50, generated by pulse laser irradiation are deposited on the surface of the positive electrode terminal member 50 that can become the roughened regions F3 and F4 in a state where the base layer 55 and the column group layer 56 are not formed, and the aluminum-derived debris particles, which are the material of the positive electrode terminal member 50, are grown into nanocolumns 561 to form the roughened regions F3 and F4, thereby forming a bristling of nanocolumns 561 of 84 nm or more, and a positive electrode terminal member 50 with high sealing properties can be obtained.
[0095] Furthermore, the method for manufacturing the battery 1 as a metal resin composite includes a filling step S31 in which molten resin MR, which is the material of the heat-melted positive electrode resin member 70, is used to fill the gaps between the numerous nanocolumns 361 constituting the column layer 36 until it reaches the base layer 35, and also fills the gaps between the numerous nanocolumns 561 constituting the column layer 56 until it reaches the base layer 55, and a solidification step S32 in which the molten resin MR filled in the gaps between the numerous nanocolumns 361 constituting the column layer 36 in the filling step S31 and the molten resin MR filled in the gaps between the numerous nanocolumns 561 constituting the column layer 56 are solidified to form the positive electrode resin member 70 bonded to the roughened regions F1 to F4, so that the positive electrode resin member 70 is bonded to the surfaces of the base layers 35, 55 and the surfaces of the nanocolumns 361, 561, and a battery 1 with high sealing properties can be obtained.
[0096] As described above, the bonding region of the lid member 30 with the negative electrode resin member 80 is roughened in the same manner as the roughened regions F1 and F2, and is forested with a large number of nanocolumnar structures with an average height of 84 nm or more, so that the bonding region of the lid member 30 with the negative electrode resin member 80 can also have high sealing properties. Furthermore, the bonding region of the negative electrode terminal member 60 with the negative electrode resin member 80 is roughened in the same manner as the roughened regions F3 and F4, and is forested with a large number of nanocolumnar structures with an average height of 84 nm or more, so that the bonding region of the negative electrode terminal member 60 with the negative electrode resin member 80 can also have high sealing properties.
[0097] It should be noted that the present embodiment is merely an example and does not limit the present invention in any way. Naturally, the present invention can be improved and modified in various ways without departing from the spirit and scope of the present invention. The following describes improvements and modifications of the present embodiment.
[0098] In this embodiment, the flat wound electrode body 40 is exemplified as the electrode body housed in the case 10, but the electrode body may be a laminated electrode body. In addition, although one electrode body is housed in the case 10 in this embodiment, multiple electrode bodies may be housed in the case 10.
[0099] In this embodiment, the case 10 has a generally flat rectangular parallelepiped shape with a bottom, but the shape of the case 10 can also be appropriately changed and may have other shapes such as a cylindrical shape. In addition, the shape of one or both of the positive electrode terminal member 50 and the negative electrode terminal member 60 may be appropriately changed. Similarly, the shape of one or both of the positive electrode resin member 70 and the negative electrode resin member 80 may be appropriately changed. Furthermore, in this embodiment, the shape of the positive electrode terminal member 50 and the shape of the negative electrode terminal member 60 are the same, but they may be different. Similarly, in this embodiment, the shape of the positive electrode resin member 70 and the shape of the negative electrode resin member 80 are the same, but they may be different.
[0100] In this embodiment, a battery 1 in which a metallic cover member 30 and a metallic positive terminal member 50 are each joined to a positive electrode resin member 70, and in which a metallic cover member 30 and a metallic negative terminal member 60 are each joined to a negative electrode resin member 80, is included in the metal resin composite of the present invention, and the unit member 1A constituting the battery 1 is also included in the metal resin composite of the present invention.
[0101] In this embodiment, the present invention is applied to a lithium ion battery, but it can be applied to any general power storage device, for example, a nickel-metal hydride battery or a nickel-cadmium battery. In addition, the use of the present invention is not limited to batteries, and it can be widely applied to composites that bond metal members and resin members.
[0102] In this embodiment, the positive electrode resin member 70 reaches the base layer 35 in the roughened regions F1, F2 and the base layer 55 in the roughened regions F3, F4. However, for example, the positive electrode resin member 70 may be filled into the gaps between the numerous nanocolumns 361 or the gaps between the numerous nanocolumns 561 in a state where it reaches as a whole the tips, the portion between the tips and the middle, approximately the middle, or the portion between the middle and the base of the nanocolumns 361, 561.
[0103] In this embodiment, the roughened regions F1 and F2 are formed over the entire bonding regions E1 and E2, but the roughened regions F1 and F2 may be formed in parts of the bonding regions E1 and E2. In this case, however, it is preferable that the roughened regions F1 and F2 are formed in an annular shape surrounding the positive electrode insertion hole 33h in the bonding regions E1 and E2. In addition, the roughened regions F3 and F4 are formed over the entire bonding regions E3 and E4, but the roughened regions F3 and F4 may be formed in parts of the bonding regions E3 and E4. In this case, however, it is preferable that the roughened region F3 is formed over the entire portion of the positive electrode terminal intermediate portion 53 in the bonding region E3. In addition, it is preferable that the roughened region F4 is formed in an annular shape along the peripheral portion of the bonding region E4. [Explanation of symbols]
[0104] 1... battery, 10... case, 20... main body member, 30... cover member, 33h…Insertion hole for positive electrode, 34h…Insertion hole for negative electrode, 50…Positive electrode terminal member, 60…Negative electrode terminal member, 70…Resin member for positive electrode, 80…Resin member for negative electrode, 30a, 50a…Protrusion, 35, 55…Base layer, 36, 56…Column group layer, 361, 561…Nanocolumnar body, E1…Cover upper surface bonding region, E2…Cover lower surface bonding region, E3…Terminal side surface bonding region, E4…Terminal lower surface bonding region, F1…Cover upper surface roughened region, F2…Cover lower surface roughened region, F3…Terminal side surface roughened region, F4…Terminal lower surface roughened region
Claims
1. A metal member having a bonding region on a surface thereof to which a resin member is bonded and which seals a gap between a first space and a second space together with the resin member, the bonding region includes a roughened region formed on the surface, in which a base layer is formed by the accumulation of debris particles, and a column group layer is formed in which the debris particles are linked together from the base layer in a string-like pattern to form nanocolumns that stand in a two-dimensional forest and extend in a height direction; A metal member, wherein the average height of the nanocolumns in the roughened region is 84 nm or more.
2. The metal member according to claim 1 , The first space is disposed outside the bonding area, and the second space is disposed inside the bonding area, The bonding region is formed in an annular shape, The roughened region is a metal member formed in an annular shape that conforms to the shape of the bonding region.
3. The metal member according to claim 1 ; a resin member joined to the joining region, A metal resin composite in which the resin forming the resin member reaches the base layer and fills the gaps between the nanocolumnar bodies.
4. The metal member according to claim 2 ; a resin member joined to the joining region, A metal resin composite in which the resin forming the resin member reaches the base layer and fills the gaps between the nanocolumnar bodies.
5. The method for producing a metal member according to claim 1 or 2, A method for manufacturing a metal member, comprising a laser irradiation step of depositing debris particles derived from the metal member, generated by irradiating the metal member with a pulsed laser, on a surface of the metal member that can become the roughened region in a state in which the column group layer is not formed, and growing the particles into nanocolumnar bodies to form the roughened region.
6. The method for producing a metal-resin composite according to claim 3 or 4, a filling step of filling the gaps between the nanocolumns constituting the column group layer with a molten resin until the gaps reach the base layer; and a solidification process in which the molten resin filled in the gaps between the nanocolumns that form the column group layer in the filling process is solidified to form a resin member joined to the roughened region.
Citation Information
Patent Citations
Resin molded body and method for manufacturing same
JP2019119093A
Battery and battery manufacturing method
JP2022079172A
Resin-metal joined body and pressure sensor
JP2018075805A